Revision of the South American grassland leafhopper genus Cortona Oman (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with description of four new species from Argentina - Duan, Yani; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2017)
The South American leafhopper genus Cortona is moved from Macrostelini to Deltocephalini and is reviewed. Its type species and four new species, C. catanachae sp. n., C. concordica sp. n., C. otamendiensis sp. n., and C. silvai sp. n., are illustrated and described from Argentina. A checklist and a key to species are provided.